ROLES OF TRADITIONAL IRRIGATION SYSTEM IN SUPPORTING RICE FARMING DEVELOPMENT: Lessons Learned from Bali Province, Indonesia - Gede Sedana (Universitas Dwijendra Press, 2023)
Agricultural development has still had significant roles on economic development in Indonesia. Rice farming is addressed to increase the productivity and quality of product by using improved agricultural practices including irrigation water management. In Bali province (Indonesia), the existence of subak as traditional irrigation system with socio-agrarian-religious in nature, could be a one of the local cultural institutions for supporting government in the food security program. The main functions of subak are distributing and allocating irrigation water among the subak’s members and between or among the subaks which are getting water from the separated dams on a similar river. These functions are supported by the implementation of internal by-laws own by each subak governing the mechanism of planting schedule, cropping patterns, water borrowing, including ritual ceremonies conducted in the relation to phases of rice planting. Subak system as social capital, therefore, could ensure the availability of irrigation water over the year. Thus, the rice farming development programmed by government could be achived by the effective subak system.